PEMBERDAYAAN KELUARGA DALAM PENINGKATAN KETAHANAN KELUARGA MELALUI STRUCTURAL FAMILY COUNSELING - Khafidhoh, Inayatul (Community Development: Jurnal Pengembangan Masyarakat Islam, 2021)
AbstractFamily empowerment is an effort to build a better family, including related to family resilience. Family resilience means that the family is able to manage and overcome problems from a psychological, economic, social and spiritual perspective. This study aims to examine increased family resilience through structural family counseling, and to describe family empowerment in increasing family resilience through structural family counseling. This study uses a mixed methods approach with a concurrent triangulation model. The data collection methods used were questionnaires, observation and interviews. Based on the results of the T-test at the 5% significance level, to test the differences in the resilience of the respondent's family before and after treatment, the p value was obtained = 0.003, where the p value was less than α (0.05). This shows an increase in the percentage level of family resilience between before being given structural family counseling and after being given structural family counseling. Supporting factors for this increase include the openness of the respondents, the willingness and readiness of the respondent to treat, and the respondent's trust in the therapist to be involved in interaction patterns and family arrangements.  Pemberdayaan keluarga merupakan usaha utuk membangun keluarga menjadi lebih baik, diantaranya terkait ketahanan keluarga. Ketahanan keluarga berati keluarga mampu mengelola dan mengatasi permasalahn dari segi psikologis, ekonomi, sosial dan spiritual. Penelitian ini bertujuan untuk menguji peningkatan ketahanan keluarga melalui structural family counseling, dan mendeskripsikan pemberdayaan keluarga dalam peningkatan ketahanan keluarga melalui structural family counseling. Penelitian ini menggunakan pendekatan mixed methods dengan model concurrent triangulatio . Metode pengumpulan data yang digunakan adalah kuesioner, observasi dan wawancara. Berdasarkan hasil uji T-test pada taraf signifikansi 5%, untuk menguji perbedaan ketahanan keluarga responden sebelum dan sesudah dilakukan treatment, diperoleh nilai p = 0,003, dimana nilai p lebih kecil dari α (0,05). Hal ini menunjukkan terjadinya peningkatan prosentase tingkat ketahanan keluarga antara sebelum diberikan structural family counseling dengan sesudah diberikan structural family counseling. Faktor pendukung peningkatan tersebut diantaranya keterbukaan dari responden, kesungguhan dan kesiapan responden dalam treatment, dan kepercayaan responden pada terapis untuk terlibat dalam pola interkasi dan tatanan dalam keluarganya.  Keyword: pemberdayaan keluarga, ketahanan keluarga, structural family counseling